A Questionable Infatuation: Toward a Solution of the TNF Issue - Kessler, Glenn Andrew (Tufts Archival Research Center, 2005)
Volume 7, Issue 1. Winter The 1979 NATO decision to modernize its theater nuclear forces remains a divisive issue not only within European politics but between the United States and its NATO allies as well. In this article Glenn Kessler argues that while the original military rationale for the 1979 communique may be questionable, the political capital invested in the decision must not now be wasted. Accordingly, both the arms control and deployment components of the 1979 decision must be preserved in order to ensure the credibility of future NATO communiques. Kessler suggests a multiphase negotiation strategy to address these imperatives.